PERAN INDONESIA INVESTMENT AUTHORITY (INA) SELAKU SOVEREIGN WEALTH FUND (SWF) DALAM MENDUKUNG PROGRAM TRANSISI ENERGI DI INDONESIA - Perdana, Radite Panji (JURNAL DARMA AGUNG, 2024)
The energy transition is a global priority in the face of climate change and energy security challenges, with Indonesia aiming to achieve net zero emissions by 2060. Sovereign Wealth Funds (SWFs) play a strategic role in supporting renewable energy investment, including the Indonesia Investment Authority (INA), which was established to attract foreign investment to support sustainable development. This research aims to examine INA's role in supporting Indonesia's energy transition through foreign investment. This research uses descriptive and normative methods with literature review to collect relevant data. The results show that INA, as an Indonesian SWF, has great potential to attract foreign investment in the development of new renewable energy and clean energy infrastructure. INA is also involved in various international cooperation and strategic projects that support the acceleration of energy transition in Indonesia. The conclusion of this study shows that INA's role is very important in the success of the energy transition, but it is necessary to optimize strategies and collaboration with various parties to achieve clean energy targets in a sustainable manner.